A study of causes of perinatal mortality in tertiary center in Bundelkhand region - Srivastava, Shilpi; Sharma, Sanjaya; Kharkwal, Sushila; Chaudhary, Vidya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The distribution of causes of death in population suggests a great potential for prevention. So the aim of study is to evaluate the cause of perinatal death in tertiary center of Bundelkhand region in M.L.B. medical college Jhansi, Uttar Pradesh (India). Methods: A retrospective study was done over a period of last one year from June 2013 to May 2014, which included total 2691 deliveries out of which 184 perinatal deaths occurred, hence perinatal mortality rate was 68.37 per 1000 birth and causes of perinatal deaths was identified and analysed. Results: Out of 68.37% perinatal mortality, majority of perinatal deaths (54.3%) occurred due to preterm low birth weight with or without associated other factors, 8.6% due to congenital anomalies, more than 38% perinatal death due to maternal factor antepartum haemorrhage, eclampsia, obstructed labour, malpresentation, medical problem in pregnancy. Conclusions: Early identification of mothers at risk of pregnancy complications through antenatal care screening, teaching pregnant women to recognize signs of pregnancy complications, timely access to obstetric care, monitoring of labour for fetal distress, and proper newborn resuscitation may reduce some of the categories of deaths. There should also be increased awareness among paediatrics and obstetrics about coordinated approach to bring down perinatal mortality.